Pro photo colorizing with GIMP - Whitt, Phillip (Digital image editor) (Apress, 2016)
Obtain techniques for adding color to black and white or monochrome photographic images using GIMP. In this book you'll also learn to create a hand-tinted effect to add an element of antiquity. Pro Photo Colorizing with GIMP also teaches techniques that enable you to selectively colorize images, mixing black and white with color. There are also tips to go the opposite way: converting color images into black and white (there's more to it than just removing color). Written with both beginning and experienced GIMP users in mind, Pro Photo Colorizing with GIMP shows you how to colorize black and white images to achieve a high degree of realism. What You'll Learn Gain a basic overview of the GIMP workspace, tools, color palettes, layers, and layer masks Learn how to make the proper tonal adjustments to black and white images before starting the colorizing process Complete simple colorizing exercises for beginners and progress to more advanced colorizing techniques Colorize skin, teeth, hair, and eyes Create a nostalgic hand-tinted look and selectively colorize (mixing color with black and white) to create interesting images Use textures and patterns to create artistic colorized images Properly convert color images into black and white Colorize black and white portraits, and re-colorize old faded color portraits Who This Book Is For GIMP users (but users of other photo editing software packages can benefit as well). It is especially useful for those who edit photographs, restore old photographs, or those who want to apply colorizing techniques for artistic effect.